Differentiated Vulvar Intraepithelial Neoplasia: What Criteria Do We Use in Practice?. Issue 3 (July 2016) - Reutter, Jason C.; Walters, Ruth A.; Selim, M. Angelica
Abstract : Objectives: We sought to recognize the working diagnostic criteria for differentiated vulvar intraepithelial neoplasia (dVIN) among expert pathologists in the field. We also sought the frequency of definitive diagnosis, terminology of equivocal lesions, and views on dVIN's biological significance. Methods: Respondents ranked 26 histological and 8 ancillary studies and 5 clinical findings as "essential, " "nonessential but strongly supports diagnosis, " "possibly supports diagnosis, " "weighs against diagnosis" or "uncertain significance or noncontributory." Consensus was defined as 75% agreement. They were asked about diagnosing dVIN on partially sampled lesions, terminology for uncertain lesions, frequency of diagnosis of dVIN relative to uncertain lesions, and if dVIN a is a precursor to an invasion. Results: Twenty-three completed the survey. Only "basal layer atypia" met consensus (86%) as essential. Consensus criteria for being at least strongly supportive of dVIN were "basal layer hyperchromasia, " "presence of basal layer mitoses, " and "large keratinocytes with abundant eosinophilic cytoplasm." Only "block-like positivity with p16" or positive HPV specific studies weighed against the diagnosis by consensus. Approximately 87% diagnosed dVIN on partially sampled lesions. Squamous cell hyperplasia with atypia was the most frequent terminology used for uncertain lesions; 87% felt dVIN is a precursor to invasion. Conclusions: Only basal layer atypia was considered diagnostically essential by consensus. Additional criteria that strongly support the diagnosis include changes affecting the basal layer and abundant eosinophilic keratinocytic cytoplasm. There was no consensus on ancillary study findings to confirm dVIN. Most would diagnose dVIN on a partial sample. Most consider dVIN a precursor to invasion. Abstract : Twenty-three experts were asked about the histopathological diagnosis of dVIN, and the only criterion essential by consensus was basal layer atypia.